Low Dose Spironolactone Monotherapy in the Management of Stage I Essential Hypertension: A Pilot Randomized, Double-Blind, Placebo-Controlled Trial - Attar, Armin (Acta Cardiol Sin, 2018)
BACKGROUND: High blood pressure (BP) is a common chronic disease needs long life drug consumption to control. Spironolactone could be used as the fourth-line therapy in patients with resistant hypertension. However, there is no study to determine the effects of low dose spironolactone as a first line therapy in treatment of essential hypertension. The aim of this study is to investigate the effect of low dose spironolactone monotherapy in management of essential hypertension. METHODS: In this double blind randomized clinical trial, 40 patients who had stage I essential hypertension were randomly divided into two groups: intervention group received spironolactone 25 milligram once daily for one month and control group received placebo once daily. At the baseline and after one month, 24-hour BP holter-monitoring and serum potassium assay were done. RESULTS: Systolic BP was reduced from 143.5 ± 8.2 mmHg to 137.10 ± 7.57 mmHg in the intervention group, while it did not change significantly in control (between group treatment difference = -4.5 mmHg, p = 0.004). There was no significant reduction of diastolic BP in the intervention group in comparison to placebo group (between group treatment difference = -1.3 mmHg, p = 0.099). CONCLUSIONS: Short course monotherapy with low dose spironolactone is effective in reducing systolic BP in patients with stage I essential hypertension.